Managing public transportation. Governance - strategies - solutions. [Themenschwerpunkt]. - (:unkn) unknown (Trialog, 2017)
Die Themen im Einzelnen: V. Benezech: Transport for tomorrow. Statement (S. 6-7); L. Sippel / J. Nolte: European passenger railservices in transition. The Fourth EU railway package brings changes and new challenges to passenger rail authorities (S. 8-11); M. Cramer / J. Müller: Repair or replace. Why the "Juncker Fund" is in contradiction with the EU's transport policy - and how it can still be turned into a success (S. 12-13); A. Kossak: Public transit and land use decisions. Review of guidebooks for transit agencies (S. 14-17); MoviCi - Urban Mobility in the Smart City. The project "MoviCi -Urban Mobility in the Smart City" connects Colombian and German researchers and practitioners (S. 18-20); W. Wunderlich / O. Mayer: PPP in Japan's railway system - a success story (S. 21-25); E.-B. Riehle / U. Hein: Managing public transport in Windhoek. The implementation of a new public bus service for Windhoek, Namibia (S. 26-29); J. Baum / E. Howe: Using GPS technology for demand data collection. Introduction to opportunities and challenges of the methodology in developing and emerging economies (S. 30-33).
Keywords: Öffentlicher Verkehr; Verkehrsplanung; Eisenbahn; Stadtverkehr; Verkehrskonzept; Mobilität; ÖPNV; Busverkehr; Stadtplanung; Umweltverträglichkeit; Verkehrsinvestition; Nachhaltigkeit; Verkehrssteuerung; Logistik; Smart City; Public-Private-Partnership